2015
DOI: 10.1177/1356336x15613968
|View full text |Cite
|
Sign up to set email alerts
|

‘…because there’s nobody who can just sit that long’

Abstract: Classroom teachers are increasingly called upon to help increase pupils’ physical activity (PA). Grounded in Guskey’s model of teacher change, this study was part of an intervention that provided classroom teachers with training for implementing classroom-based PA (CBPA). The study examined teachers’ attempts to implement CBPA and focused on their self-reported practices (number of CBPAs implemented and management routines used) as well as their perceptions of this process. Participants ( N = 13) were teachers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
30
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 22 publications
7
30
0
9
Order By: Relevance
“…Articulating a connection between improved student focus with physical activity is consistent with other research (Dinkel et al, 2017;Gately et al, 2013;Gibson et al, 2008, Martin & Murtagh, 2015Stylianou et al, 2016). Orlick (2012) described focus as an essential skill for learning, distraction control, and mental readiness, but acknowledged that the skill is often expected and not taught.…”
Section: Improved Student Focussupporting
confidence: 71%
“…Articulating a connection between improved student focus with physical activity is consistent with other research (Dinkel et al, 2017;Gately et al, 2013;Gibson et al, 2008, Martin & Murtagh, 2015Stylianou et al, 2016). Orlick (2012) described focus as an essential skill for learning, distraction control, and mental readiness, but acknowledged that the skill is often expected and not taught.…”
Section: Improved Student Focussupporting
confidence: 71%
“…As such there was suggestion that schools may have a tendency to support more traditional forms of teaching. Whilst external pressures such as meeting curriculum requirements (Cothran et al, 2010;Stylianou et al, 2016) have been identified in previous literature, this issue of school inspection is a particularly novel finding, which has not previously been reported.…”
Section: Discussionmentioning
confidence: 72%
“…This point very much aligns with previous data drawing upon diffusion of innovation theory suggesting the potential for observability (the perception that the innovation will produce observable results for key members of the social system) to influence teachers adoption of MI . The issues of simple to implement and accessible resources and the need for face-to-face professional development involving practical modelling of ideas has also been addressed in recent work by Stylianou et al (2016), who suggested that resources must be simple to implement, easy to access and developmentally appropriate; and that professional development training should be continuous and involve management strategies as a core component.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations